2010
DOI: 10.1111/j.1447-0594.2010.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D hormone: A multitude of actions potentially influencing the physical function decline in older persons

Abstract: Vitamin D, a secosteroid (pro)-hormone, has been traditionally considered as a key regulator of bone metabolism, and calcium and phosphorous homeostasis through a negative feedback with the parathyroid hormone. However, during the last twenty years, the role played by vitamin D has been largely revised by recognizing it a pleiotropic action on a wide spectrum of systems, apparati, and tissues. Thus, vitamin D has growingly been involved as a primary determinant of biological modifications and specific clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 116 publications
(204 reference statements)
0
44
0
2
Order By: Relevance
“…An extensive literature exists on the association between vitamin D deficiency and sarcopenia (reviewed by Cesari et al 2011), but proof of causality and pathogenetic mechanisms are still controversial (Stockton et al 2011). Nevertheless, a recent study reported that vitamin D supplementation to severely deficient persons produced marked improvements in fatigue that were accompanied, and perhaps mediated by augmented mitochondrial function, as measured in vivo by 31 P-NMR spectroscopy (Sinha et al 2013).…”
Section: Impact Of Age-related Conditions On Muscle Mitochondrial mentioning
confidence: 99%
“…An extensive literature exists on the association between vitamin D deficiency and sarcopenia (reviewed by Cesari et al 2011), but proof of causality and pathogenetic mechanisms are still controversial (Stockton et al 2011). Nevertheless, a recent study reported that vitamin D supplementation to severely deficient persons produced marked improvements in fatigue that were accompanied, and perhaps mediated by augmented mitochondrial function, as measured in vivo by 31 P-NMR spectroscopy (Sinha et al 2013).…”
Section: Impact Of Age-related Conditions On Muscle Mitochondrial mentioning
confidence: 99%
“…For example, selected nutrient deficits might underlie the relationship between kidney function and frailty. Indeed, vitamin D deficiency, which is highly prevalent among elders, may predispose to osteoporosis and related complications, such as vertebral fractures (Cesari et al 2011). Interestingly, it has been recently demonstrated that vitamin D supplementation improved muscle strength, functional ability, and balance in patients with reduced eGFR and vitamin D deficit undergoing conservative or peritoneal dialysis treatment (Taskapan et al 2011).…”
Section: Impact Of Egfr On Predictive Accuracy Of Frailtymentioning
confidence: 99%
“…Indeed, vitamin D deficiency, which is highly prevalent among elders, may predispose to osteoporosis and related complications, such as vertebral fractures 55 and, then, postural instability. Furthermore, vitamin D deficit preferentially weakens hip and thigh muscles, which are primarily involved in dynamic balance.…”
mentioning
confidence: 99%